The Effect of AI and Digital Literacy on English for Public Speaking Proficiency - Arumsari, Arumsari; Rimawati, Elistya; Octaviani, Saly Kurnia (Universitas Pahlawan Tuanku Tambusai, 2026)
Integrating technology into English language learning is essential for enhancing public speaking proficiency in the digital era. However, the specific impact of Artificial Intelligence (AI) tools versus general digital literacy on speaking performance remains underexplored. This study aims to analyze the simultaneous and partial effects of digital literacy and AI usage on students' English for Public Speaking proficiency. Using a quantitative approach, data were collected from 35 second-semester students and analyzed using multiple linear regression. The findings reveal that while digital literacy partially shows no significant effect, AI usage positively and significantly influences speaking skills. Simultaneously, both variables contribute 38.1% to the proficiency model. It is concluded that while digital literacy facilitates access, direct AI-assisted practice serves as the primary driver for improving public speaking competence.